Self-Initiated Professional Development among Malaysian TVET Teachers in Vocational Colleges - Leenna Bte Abdul Rahman, Nur; Binti Mokhtar, Mahani; Farzeeha Binti Ali, Dayana (International Journal of Psychosocial Rehabilitation, 2020)
This concept paper will present a discussion on self-initiated professional development (SI-PD) among Malaysian TVET teachers in vocational colleges. Self-initiated or self-directed professional development has gained much attention lately. Since there is an increasing concern that teachers’ professional development needs to be effective and meaningful. Furthermore, one of the Ministry of Education’s (MOE) agendas in the Malaysia Education Blueprint (MEB) 2013-2025 is to transform continuous professional development (CPD) practice by increasing self-led professional development and reducing ministry-led professional development from 16 percent to 60 percent by the year 2025. Self-initiated professional development practices provide teachers with the autonomy to direct their own learning. This paper presents a compilation of critical reviews of reports, journals, and articles by previous authors and researchers on self-initiated professional development and aims to gain perspectives from TVET teachers in vocational colleges on the needs of a self-initiated professional development framework.